Measuring the Role of the Police in Preventing Criminal Acts of Obscenity - Ambarani Shelia, Putri; Ekawaty Ismail, Dian; Yutye Imran, Suwitno (Estudiante Law Journal, 2024)
This study aims to determine the police's efforts in tackling the crime of child abuse, and to find out the factors that hinder the police in handling cases of child abuse in the jurisdiction of the Bone Bolango Police. The type of research used is empirical research with a case approach. The results of the study show that the police's efforts to deal with criminal acts of child molestation are carried out through preventive and repressive efforts. Preventive efforts are anticipating sexual immorality by providing legal counseling, the negative effects of promiscuity among students, and carrying out raids or patrols to ensure a sense of security in society. Repressive efforts, namely by disclosing the occurrence of criminal acts of obscenity by conducting investigations,